Successful Implementation of Expanded Newborn Screening in the Philippines Using Tandem Mass Spectrometry - Carmencita D. Padilla; Bradford L. Therrell; Maria Melanie Liberty B. Alcausin; Mary Anne D. Chiong; Mary Ann R. Abacan; Ma. Elouisa L. Reyes; Charity M. Jomento; Maria Truda T. Dizon-Escoreal; Margarita Aziza E. Canlas; Michelle E. Abadingo; J. Edgar Winston C. Posecion; Conchita G. Abarquez; et al. (MDPI AG, 2022)
Newborn bloodspot screening (NBS) began as a research project in the Philippines in 1996 and was mandated by law in 2004. The program initially included screening for five conditions, with a sixth added in 2012. As screening technology and medical knowledge have advanced, NBS programs in countries with developed economies have also expanded, not only in the number of newborns screened but also in the number of conditions included in the screening. Various approaches have been taken regarding selection of conditions to be screened. With limited resources, low- and middle-income countries face significant challenges in selecting conditions for screening and in implementing sustainable screening programs. Building on expansion experiences in the U.S. and data from California on Filipinos born and screened there, the Philippine NBS program has recently completed its expansion to include 29 screening conditions. This report focuses on those conditions detectable through tandem mass spectrometry. Expanded screening was implemented in a stepwise fashion across the seven newborn screening laboratories in the Philippines. A university-based biochemical genetics laboratory provides confirmatory testing. Follow-up care for confirmed cases is monitored and provided through the NBS continuity clinics across the archipelago. Pre-COVID-19 pandemic, the coverage was 91.6% but dropped to 80.4% by the end of 2020 due to closure of borders between cities, provinces, and islands.